The morphological, biological and genetic characteristics of low nuclear grade breast carcinoma and their putative precursor lesions - Abdel-Fatah, Tarek Mohamed A. (2010)
There is evidence to suggest that some special types of breast cancer including tubular and lobular carcinoma and their putative precursor lesions including atypical ductal hyperplasia (ADH), low grade ductal carcinoma in-situ (DOS) and lobular neoplasia (LN) may consist in a family of interrelated lesions. Recently, an attention has been focused on the columnar cell lesion as an early non-obligate precursor lesion of breast cancer.